THE VISCOELASTIC MODEL OF STEEL WIRE ROPE RUBBER CONVEYOR BELT AND THE ANALYSIS OF DEPRESSION RESISTANCE UNDER THE INFLUENCE OF TEMPERATURE - CHEN HongYue; XU RuoYong; MAO Jun (Jixie qiangdu)
To study the conveyor belt cover and roller resistance variation with the operation process of belt conveyor,based on the three components of solid model,considering the influence of temperature on the conveyor belt viscoelasticity properties,put forward and set up a three element four variables considering temperature thermal viscoelastic kinetic parameter model.Then using the variable temperature dynamic compression experiment,getting the dynamic loading force under different temperature and time of curve,through first-order Fourier series fitting and obtained the conveyer belt rubber layer is derived formula of the thermal viscoelastic Kinetic parameter model and the accuracy of the formula are verified,finally established contains parameters such as temperature,tape speed of conveyor belt rolling resistance coefficient calculation equation,analyses the various factors affecting the impact on the rolling resistance coefficient,and through experiment verification rolling resistance coefficient calculation equation for the test,the results of the study to guide saving energy running of the belt conveyor control to provide the basis.